2023
DOI: 10.12688/f1000research.73587.2
|View full text |Cite
|
Sign up to set email alerts
|

Teaching-learning behavior in medicine according to students’ perspective: what most influences academic achievement?

Abstract: Background: The medical student is a part of education that has a pivotal role in contributing to the teaching-learning process. Assessing the learning process by student perception can give valuable input to predict academic achievement. This study aims to identify the student’s perspective regarding teaching-learning behaviour and which factor most influences academic achievement. Methods: A total of 443 medical students of the preclinical phase were selected to participate in this study. Design of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Student learning efficacy in medical education is affected by a broad spectrum of factors, including learning experiences, assessment efficacy, emotional and socioenvironmental influences, organizational dynamics, and educational content relevance. 36 , 37 , 38 Past studies in VR technology’s role in medical education highlight its varying effectiveness. Kim and Kim 39 in 2023 found that less immersive VR environments may enhance knowledge outcomes, while Huang et al 40 in 2016 noted the benefits of immersive and imaginative VR elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Student learning efficacy in medical education is affected by a broad spectrum of factors, including learning experiences, assessment efficacy, emotional and socioenvironmental influences, organizational dynamics, and educational content relevance. 36 , 37 , 38 Past studies in VR technology’s role in medical education highlight its varying effectiveness. Kim and Kim 39 in 2023 found that less immersive VR environments may enhance knowledge outcomes, while Huang et al 40 in 2016 noted the benefits of immersive and imaginative VR elements.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual Reality Training for Teaching Personal Protective Equipment Skills of learning outcomes in VR training. Student learning efficacy in medical education is affected by a broad spectrum of factors, including learning experiences, assessment efficacy, emotional and socioenvironmental influences, organizational dynamics, and educational content relevance [36][37][38]. Past studies in VR technology's role in medical education highlight its varying effectiveness.…”
mentioning
confidence: 99%